Physical Fitness of the Elderly Viewed from Physical ActivityAt the Telkomsel Banjarbaru Retiree Association - Puteri Febrena Fauzy; Ramadhan Arifin; Mita Erliana (Universitas Negeri Semarang, 2025)
The purpose of this study was to determine the physical fitness of the elderly seen from physical activity at the Telkomsel Banjarbaru Retiree Association. Researchers used a quantitative descriptive method with a physical fitness measurement test method the test was collected with 2 minuts step in place and questionnaires on participants of the Telkomsel Banjarbaru Retiree Association. The population in this study was the elderly P2Tel Banjarbaru which amounted to 30 people, sample selection based on purposive sampling technique with a total sample of 23 elderly who met the criteria. The results of the Banjarbaru city elderly physical fitness test showed that in the category below average (34.78%), average (56.52%), above average (8.70%). The results of the Banjarbaru city elderly physical activity survey were classified as good (8.70%), sufficient (86.96%), low (4.35%), very low (0.00%). The conclusion from the results of the study that the physical fitness of the elderly in the Telkomsel Banjarbaru Retiree Association is in the average category and the physical activity of the elderly in the Telkomsel Banjarbaru Retiree Association is in the sufficient category.